Peran Posbindu dalam Upaya Memberdayakan Kesehatan Diri Lansia (Studi Kasus di RW 01 Kelurahan Situ Gede, Kecamatan Bogor Barat, Kota Bogor) - Deniza Lustyana Kusumah; Ninuk Purnaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Empowerment of elderly self-health in RW 01 Situ Gede Village can begin through the role of Posbindu Melati. Posbindu activities encourage the realization of empowerment of the elderly to increase health awareness. The purpose of this study is to 1) to describe the Posbindu Melati program; 2) to identify the health conditions of the elderly in RW 01, Situ Gede Urban Village; 3) to analyze the achievement of the principle of empowerment; 4) as well as analyzing the impact and response of the community related to the Posbindu Program. Methods in this study were obtained through observation, interviews, documentation studies, as well as direct health examination practice. The results showed that the elderly's self health empowerment program in Posbindu Melati included health checks, elderly gymnastics, and health promotion. The program supports the improvement of erderly’s health which can be accepted in a healthy condition, only a few elderly who have complaints of non-communicable diseases (PTM). The implementation of the principle of empowerment has also been successful in empowering the self-health of the elderly. The impact obtained from the Posbindu Melati program is that elderly become more aware of health problems so that they pay more attention to their daily lifestyle. The role of Posbindu Melati in empowering the health of the elderly has also received a positive responses from the community. Keywords: elderly, empowerment, health, posbindu program